2017
DOI: 10.1002/mame.201700227
|View full text |Cite
|
Sign up to set email alerts
|

Ionically Crosslinked Thermoresponsive Chitosan Hydrogels formed In Situ: A Conceptual Basis for Deeper Understanding

Abstract: In situ formation and the performance of ionically crosslinked thermosensitive chitosan‐based hydrogels are presented. Experimental analyses, together with mechanistic descriptions of the events during hydrolysis, are employed to uncover the role of urea and isobutanol as chemical modifiers by comparing three classes of hydrogels formed in chitosan/β‐glycerolphosphate (β‐GP) solutions. Rheological measurements demonstrate that urea caused an increase in gelation time and temperature of chitosan/β‐GP systems, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Nowadays, disposal of polymer wastes in landfills is a serious challenge in the developing countries, for disposed polymer wastes are permanent contaminants to the local environment including soil and water. This underlines the need for the development of biodegradable polymer composites [1][2][3][4][5]. On the other hand, the competitive market demands a delicate balance between the cost and the performance of the new products.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, disposal of polymer wastes in landfills is a serious challenge in the developing countries, for disposed polymer wastes are permanent contaminants to the local environment including soil and water. This underlines the need for the development of biodegradable polymer composites [1][2][3][4][5]. On the other hand, the competitive market demands a delicate balance between the cost and the performance of the new products.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers are one of the most common materials that have been used for fabrication of tissue engineering scaffolds. Natural polymers (collagen, gelatin, chitosan, etc.) have shown more similarity to the composition of the body following better interaction with cells .…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is another example of a natural ionic hydrogel system. Chitosan is a cationic polysaccharide derived from the exoskeleton of prawns and other crustaceans. , Kim et al and Moura et al have reported chitosan ionically cross-linking with multivalent anions such as PO 3– ions, in particular, β-glycerolphosphate, to yield highly biocompatible hydrogels. , …”
Section: Introductionmentioning
confidence: 99%